Successional floristic analysis in the Cerro Huitepec biological station, Chiapas, Mexico - Ramirez-Marcial, Neptali; Ochoa-Gaona, Susana; Gonzalez-Espinosa, Mario; Quintana-Ascencio, Pedro F. (Instituto de Ecología, A.C., 1998)
A floristic checklist and a vegetation account of six successional communities: grassland, shrubland, early forest, mid-successional forest, oak forest, and evergreen cloud forest in the privately-owned biological station at Cerro Huitepec, San Cristóbal de Las Casas, Chiapas, México, is presented. A total of 83 vascular plant families including 186 genera and 315 species were recorded. We found that 10% of the species are annual herbs, 50% herbaceous perennials, 20% shrubs, 17% understory trees, and 3% canopy trees. An analysis by means of the Jaccard similarity index showed three distinct vegetational groups. The first group is defined by pioneer and early successional species of grassland and shrubland communities that show 58% of floristic similarity; the second group includes species of the early forest and mid-successional forest communities which show 52% of floristic similarity; the third group, represented by a high number of mid- and late successional shrub and tree species, typical of mature habitats like the oak forest and evergreen cloud forest communities, shows 57% of floristic similarity. Although the Estación Biológica Cerro Huitepec includes 32% of the floristic richness estimated for the area situated in central Chiapas above the elevation of 2000 m, due to the low density of many species, and the relatively fast deforestation rates of neighboring areas, the flora at the station may suffer some local extinctions in the future if appropriate management strategies are not considered.